Canadian Contractural Duress and Criminal Duress: "Irrational, Anomalous, Perverse, Illogical and Fundamentally Wrong" or Just Misunderstood? - Frances E. Chapman (Washington University Global Studies Law Review, 2012)
The contractual and criminal bases for duress in Canada, the United States, and the Commonwealth are currently in disrepair. Contract law serves to enforce binding agreements that are reflective of our choices, but duress threatens to nullify that very purpose. In addition to the contractual basis of duress, the law of duress has developed from a criminal defense perspective, but it has been difficult to apply. Controversy surrounds the defense particularly where the threats involve the sacrifice of an innocent person. Only by examining the philosophical, historical, and current state of this defense in the civil and criminal context can one begin to repair and reformulate the defense of duress for future application.
Keywords: duress; contract law